2021
DOI: 10.1093/plphys/kiab376
|View full text |Cite
|
Sign up to set email alerts
|

CRISPR/Cas9 mutants of tomato MICRORNA164 genes uncover their functional specialization in development

Abstract: Plant microRNA164 (miR164) plays diverse regulatory functions by post-transcriptional repression of certain NAC-domain transcription factors. However, the involvement of miR164 in fleshy fruit development and ripening remains poorly understood. Here, de-novo prediction of tomato (Solanum lycopersicum) MIR164 genes identified four genes (SlMIR164a-d), of which SlMIR164d has an atypically long pre-miRNA. The roles of the fruit expressed SlMIR164a, b and d were studied by analysis of their CRISPR mutants. The slm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 52 publications
0
18
0
Order By: Relevance
“…To further determine the regulation of Sl-MIR164a on the transcript level of SlNAM3, we generated miR164a/b-5p-silenced tomato plants using short tandem target mimic (STTM) technology (Figure S2a). Although silencing all the mature miR164 members in STTM164 resulted in abnormal shoot development (Gupta et al, 2021), the STTM164a/b-5p plants exhibit normal development with miR164a/b-5p silencing (Figure 3a). Exposure to cold at 4°C obviously induced the transcript level of SlNAM3 both in STTM164a/ b-5p and WT plants, with the induction being more significant in STTM164a/b-5p plants (Figure 2d).…”
Section: Interaction Between Sl-mir164a and Slnam3mentioning
confidence: 99%
See 1 more Smart Citation
“…To further determine the regulation of Sl-MIR164a on the transcript level of SlNAM3, we generated miR164a/b-5p-silenced tomato plants using short tandem target mimic (STTM) technology (Figure S2a). Although silencing all the mature miR164 members in STTM164 resulted in abnormal shoot development (Gupta et al, 2021), the STTM164a/b-5p plants exhibit normal development with miR164a/b-5p silencing (Figure 3a). Exposure to cold at 4°C obviously induced the transcript level of SlNAM3 both in STTM164a/ b-5p and WT plants, with the induction being more significant in STTM164a/b-5p plants (Figure 2d).…”
Section: Interaction Between Sl-mir164a and Slnam3mentioning
confidence: 99%
“…In strawberry ( Fragaria vesca ), miR164 targets NAC protein 38 and 87 and is involved in fruit senescence under low temperatures (Li et al., 2017). The tomato miR164 ( Sl‐miR164 ) is encoded by four SlMIR164 genes, and two major genes Sl‐MIR164a and Sl‐MIR164b produce the same mature miRNA ( Sl‐miR164a/b‐5p ) which are much more frequently identified in the published small RNA data than the other two Sl‐miR164 genes (Gupta et al., 2021). However, the role of the miR164‐NAC module in the cold tolerance of tomato has yet to be revealed.…”
Section: Introductionmentioning
confidence: 99%
“…During prickly pear cactus fruit development, miR164 expressed in all fruit development stages and homogenously expressed in fruit-related organs [59]. miR164 deficient mutant tomato slmir164aCR possessed smaller fruit than wild type indicating its role in regulating fruit development [29]. Mostly, miR164 regulates fruit development by targeting NAC transcription factors, such as CUP-SHAPED COTYLEDON2 (CUC2).…”
Section: Discussionmentioning
confidence: 99%
“…Comparing miRNA abundance in three developmental stages between wild and cultivated pepper fruits, miR159 and miR172 probably were proposed possibly affecting fruit set and fruit size [28]. Based on CRISPR/Cas9-mediated knock-out of miR164 in tomato, miR164 deficient mutant developed smaller fruit than wild type fruit mainly caused by reduced pericarp cell division and expansion [29].…”
Section: Introductionmentioning
confidence: 99%
“… Liu et al (2016) revealed that GA- and IAA-mediated miRNAs and their target auxin response factors (ARFs) affect the formation of pericarp cell layers during tomato fruit development, suggesting that phytohormones may regulate pericarp thickness. The loss of function of SlGPAT6 led to decreased pericarp thickness by altering the expression level of the gene regulating the formation and remodeling of the cuticle and cell wall ( Petit et al, 2016 ), Gupta et al (2021) revealed that SlMIR164a is the major contributor of sly-miR164 in tomato fruit pericarp and plays a critical role in epicarp expansion. SlMIR164a CRISPR/Cas9-derived mutants exhibited thinner fruit pericarp from approximately 10 to 15 DAP than the wild type.…”
Section: Introductionmentioning
confidence: 99%